Implementation and Investigation of an Advanced Induction Machine Field-Oriented Control Strategy Using a New Generation of Inverters Based on dSPACE Hardware - Es-saadi, Mouna; Chaikhy, Hamid; Khafallah, Mohamed (Applied system innovation, 2022)
Widely used in industrial applications, the induction machine is the subject of many researches. Many are aimed at developing its performances, such torque ripples, current distortions or even rotor speed response, by using different control strategies or even replacing two level inverters in a field oriented control strategy with a new generation of inverters. This paper presents an advanced asynchronous machine field-oriented control strategy with a three level neutral point clamped inverter. The attractive performances of the field oriented control strategy using a three level neutral point clamped inverter are experimentally tested. Both conventional and new field-oriented control strategies are implemented in a dSPACE board induction machine. To highlight the advantages of the new control strategy, conventional and improved strategies are studied in open loop and closed loop conditions using integral proportional and proportional integral controllers, in term of current distortions, torque and speed response.